Development of Learning Media Using the KineMaster Application for Learning English Class V SDN 065853 Tegal Sari Mandala II Kec. Denai Medan - Michael Yobel Halomoan Siburian (Asian Journal of Applied Education (AJAE), 2023)
The research aims to determine the feasibility, practicality, and effectiveness of learning media using the Kine Master application in learning English for class V SDN 065853 Tegal Sari Mandala II T.A. 2022/2023. This type of research is R&D (Research and Development) using the 4D (Four-D) model which consists of Define, Design, Develop, and Disseminate. The subjects in the study were fifth grade students at SDN 065853 Tegal Sari Mandala II, Kec. Medan Denai, T.A 2022/2023. The object in this study is a learning medium using the Kine Master application. The results of this study indicate that learning media using the KineMaster application for learning English is very feasible. Validation results by media experts obtained a percentage score of 93.33% with very feasible criteria, then material validation by material experts obtained a score percentage of 93.84% with very feasible criteria, practicality validation was carried out by practical experts obtained a score percentage of 100% with very practical criteria , in field trials by carrying out learning outcomes tests obtained an average effectiveness of 88.6 with effective criteria. So it can be concluded that the learning media uses the KineMaster application in learning English for class V SDN 065853 Tegal Sari Mandala II, Kec. Medan Denai, very feasible, very practical, and effective for use in the learning process.